Pengaruh Citra Merk, Harga Dan Promosi terhadap Keputusan Pembelian Smartphone pada Counter Zombri Cell Muara Bulian - Ahmad Fithoni; Desi Fitriyani (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2022)
The purpose of this study was to determine the effect of brand image, price and promotion on smartphone purchasing decisions at the Muara Bulian Zombri Cell Counter. The study was conducted quantitatively descriptive with the number of respondents as many as 68 people while the analysis used was multiple regression, partial test (t test), Simultaneous test (f test), and determination test (R2). The results showed that the independent variable that had the most influence on smartphone purchasing decisions was the price variable (X2) with tcount (10,969) then Promotion (X3) with tcount (8.973) and finally Brand Image (X1) with tcount (8.396). For Fcount = 101.212 > Ftable = 2.69 This means that together Brand Image, Price and Promotion affect consumer purchasing decisions. Meanwhile, seen from the coefficient of determination. Brand Image, Price and Promotion affect smartphone purchase decisions at the Zombri Cell Counter Muara Bulian by 73.4% and the remaining 26.6% is influenced by other factors not examined in this study.